Kontribusi Kompetensi Profesional, Komitmen Integritas, Kemampuan Adaptasi, dan Kepuasan Organisasi terhadap Transformasi Sumber Daya Manusia Polri - BWS, Didit; Rahman, Muhammad Afifi (Jurnal EMT KITA, 2026)
This study aims to analyze the contribution of professional competence, integrity commitment, adaptability, and organizational satisfaction to the transformation of human resources (HR) in the Indonesian National Police (Polri). HR transformation is central to police reform, involving the enhancement of professionalism, ethics, and adaptability to technological developments and societal demands. The study uses a literature review method, examining 50 scholarly articles, national and international journals, and official Polri reports from the last ten years (2015–2025). The findings indicate that professional competence improves technical skills and decision-making, integrity commitment strengthens ethics and compliance, adaptability enables members to respond to internal and external changes, while organizational satisfaction drives motivation and loyalty. The integration of these four factors significantly contributes to HR transformation, enhancing public service quality, operational effectiveness, and technology adoption. The literature also highlights the need for competency development based on organizational needs, consistent ethical practices, strategies to enhance adaptability, and management of member satisfaction through a supportive work environment. These findings provide a foundation for Polri policymakers to design effective, sustainable, and adaptive HR transformation strategies in response to social and technological dynamics.